The Role of Transient Receptor Potential Vanilloid 4 in Pulmonary Inflammatory Diseases - Scheraga, Rachel G.; Southern, Brian D.; Grove, Lisa M.; Olman, Mitchell A. (Frontiers in Immunology, 2017)
Ion channels/pumps are essential regulators of organ homeostasis and disease. In the present review we discuss the role of the mechanosensitive cation channel, transient receptor potential vanilloid 4 (TRPV4), in cytokine secretion and pulmonary inflammatory diseases such as asthma, cystic fibrosis, and acute lung injury/acute respiratory distress syndrome (ARDS). TRPV4 has been shown to play a role in lung diseases associated with lung parenchymal stretch or stiffness. TRPV4 indirectly mediates hypotonicity-induced smooth muscle contraction and airway remodeling in asthma. Further, the literature suggests that in cystic fibrosis TRPV4 may improve ciliary beat frequency (CBF) enhancing mucociliary clearance, while at the same time increasing pro-inflammatory cytokine secretion/lung tissue injury. Currently it is understood that the role of TRPV4 in immune cell function and associated lung tissue injury/ARDS may depend on the injury stimulus. Uncovering the downstream mechanisms of TRPV4 action in pulmonary inflammatory diseases is likely important to understanding disease pathogenesis and may lead to novel therapeutics.